The Impact of Integrated Marketing Communications Dimensions on Improving Customers Experience in Coastal Tourism Industry - Ali Asghar Tabavar (پژوهش‌های مدیریت عمومی, 2019)
Abstract The purpose of this study was to analyze the factors affecting integrated marketing communication and provide solutions for improving the customer experience in Chabahar coastal tourism industry. This research is applied in terms of its purpose and is a survey research in terms of its implementation. The statistical population of the study includes all tourists who have traveled to Chabahar during November 2017 to September 2018. The number of samples selected by random cluster sampling method was 385 for tourists. A total of 400 questionnaires were distributed in which 385 questionnaires were returned. In order to collect data, a questionnaire was used. For this purpose, two researcher-made questionnaires of integrated marketing communication and customer experience were used. Statistical analysis (regression and Friedman test) was used to analyze the data. According to the findings of this study, the independent variable of integrated marketing communications has a positive and significant effect on the dependent variable of improving customer experience. In the order of the components of direct sales and marketing, there is a positive and significant impact on the improvement of customer experience. Considering the positive impact of the double sale of direct sales and marketing, the need to pay more attention to them is a must. Introduction Chabahar is in the free zones this will lead to foreign investment attraction, export promotion, increased revenues from foreign investment, and the creation of suitable employment opportunities for the labor force and attracting tourists to the region. The necessity of such a research can be arranged in a way that the development of organizational units such as market development, public relations and etc. in the Chabahar coastal area for ​​tourism problems such as inconsistency between them, conflicting and conflicting goals, as well as the absence of harmony in the message It has attracted customers and stakeholders. The huge volume of TV advertising, the heavy budget of the Public Relations Unit and their various promotional programs has become a serious issue for top executives in the region, with the effectiveness of the costs being spent only through an integrated approach. Case study   The overall aim of this study is to examine the factors affecting integrated marketing communication and provide solutions for improving customer experience. With the passage from traditional economics and the intensification of competition in new dimensions, the customer has become the core of all the activities of organizations, so that from a competitive perspective, the survival of organizations depends on identifying and attracting new customers and maintaining the available Customers. Studies show that tourism, along with advanced industries, has a good future. Tourism is the main industry in many countries and plays a major role in the development of the global economy. As the importance of service modalities in advanced economies has increased, special issues in service marketing have attracted increasing attention. Provision of appropriate services to customers is one of the most important factors in creating a distinction between tourism industries in a competitive environment. Materials and methods The present study is applied research because its purpose is to develop knowledge. And descriptive research based on survey type. The instrument used in this research is a researcher-made questionnaire, whose validity was confirmed by the experts. Reliability of the questionnaire was obtained using Cronbach's alpha. Data were analyzed by SPSS software. The statistical population of this study includes all tourists who travel to the coastal area of ​​Chabahar and are unlimited. A sample of 385 people was selected using Morgan table. They were selected using randomized cluster sampling. To each of the elements of the community to select the equal chance to choose. Discussion and Results Indicators of central tendency and dispersion tendencies of direct sales and marketing are respectively 3.84 and 3.79 respectively. The first subset of the research showed that promotion of sales has a positive and significant effect on improving customer experience. The second sub hypothesis shows that direct marketing has a positive and significant impact on improving customer experience. According to two sub-hypotheses, the main hypothesis was proved; the results showed that integrated marketing communications have a positive and significant effect on improving customer experience. Conclusions In line with the objectives of this research, a major hypothesis and two sub-hypotheses were introduced. Which was confirmed after analyzing the data and the results of the regression test. The research findings showed that sales promotion was effect in improving customer experience. Therefore, it is suggested that managers, decision makers and planners should hold coastal competitions along with the awarding of seasonal and concessional awards (cash and non-cash) to enhance and improve the customer experience, in seasons where the climate of the Chabahar coastal tourism zone is more suitable. The findings of the research indicate that direct marketing has a direct impact on improving customer experience. And it is recommended to create national markets, handicrafts centers and create booths on the coast In order to preserve and revitalize traditional arts and crafts, including the special needlework for women of the Baloch artist, to improve this goal.